Intra-seasonal variation of injury patterns among German Bundesliga soccer players - Leventer, L.; Eek, F.; Lames, M. (Journal of Science and Medicine in Sport, 2019)
Objective: High fluctuations in injury-risk during the playing season in soccer have been reported. As seasons are structured in periods with homogenous loads and intensities, we investigated injury-risk over season periods, contrarily to previous studies adopting a month-based approach. Design: Cohort study; Level of evidence, 2. Methods: Incidence-rate ratios (IRRs) for match and training injuries were compared across six consecutive seasons of German Bundesliga, divided into six periods each: Pre-season (PS), winter-break (WB), quarter 1-4: (Q1-Q4).